Quantification of biopharmaceuticals and biomarkers in complex biological matrices: a comparison of liquid chromatography coupled to tandem mass spectrometry and ligand binding assays. (August 2015) - Bults, Peter; van de Merbel, Nico C; Bischoff, Rainer
<x xml:space="preserve">Abstract</x> The quantification of proteins (biopharmaceuticals or biomarkers) in complex biological samples such as blood plasma requires exquisite sensitivity and selectivity, as all biological matrices contain myriads of proteins that are all made of the same 20 proteinogenic amino acids, notwithstanding post-translational modifications. This review describes and compares the two main approaches, namely, ligand binding assays (LBAs) and liquid chromatography coupled to tandem mass spectrometry in the selected reaction monitoring (SRM) mode. While LBAs remain the most widely used approach, SRM assays are gaining interest due to their generally better analytical performance (precision and accuracy) and their capacity for multiplex analyses. This article focuses on the possible reasons for the discrepancies between results obtained by LBAs and SRM assays.